Specificity of Activated CryIA Proteins from Bacillus thuringiensis subsp. kurstaki HD-1 for Defoliating Forest Lepidoptera - van Frankenhuyzen, K. (1991)
The insecticidal activity of the CryIA(a), CryIA(b), and CryIA(c) toxins from Bacillus thuringiensis subsp. kurstaki HD-1 was determined in force-feeding experiments with larvae of Choristoneura fumiferana, C. occidentalis, C. pinus, Lymantria dispar, Orgyia leucostigma, Malacosoma disstria, and Actebia fennica. The toxins were obtained from cloned protoxin genes expressed in Escherichia coli. The protoxins were activated with gut juice from Bombyx mori larvae. Biological activity of the individual gene products as well as the native HD-1 toxin was assessed as the dose which prevented 50% of the insects from producing frass within 3 days (frass failure dose [FFD(50)]). The three toxins were about equally active against M. disstria. In the Choristoneura species, CryIA(a) and CryIA(b) were up to fivefold more toxic than CryIA(c). In the lymantriid species, CryIA(a) and CryIA(b) were up to 100-fold more toxic than CryIA(c). The toxicity of HD-1 was similar to that of the individual CryIA(a) or CryIA(b) toxins in all of these species. None of the CryIA toxins or HD-1 exhibited and toxicity towards A. fennica. Comparison of the observed FFD(50) of HD-1 with the FFD(50) expected on the basis of its crystal composition suggested a possible synergistic effect of the toxins in the two lymantriid species. Our results further illustrate the diversity of activity spectra of these highly related proteins and provide a data base for studies with forest insects to elucidate the molecular basis of toxin specificity.